2004
DOI: 10.1002/jsfa.1881
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of protein concentrates from ungerminated and germinated fluted pumpkin (Telfairia occidentalis Hook) seeds in cookie formulations

Abstract: Cookies (soft type biscuits) were produced from blends of wheat flour containing graded levels (0-25%) of protein concentrates prepared from ungerminated and germinated fluted pumpkin (Telfairia occidentalis Hook) seeds and evaluated for nutritional, baking and sensory properties. Protein quality was investigated using weanling albino rats fed diets that were formulated to supply 10% protein using cookie samples, with casein as a control. Cookies produced from blends containing protein concentrates from germin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 25 publications
4
24
1
Order By: Relevance
“…Flour contained ash content (0.48 %), SDS, sedimentation value (30.19 %) and diastatic activity of 265 mg/10 g flour. Singh et al(1993) reported similar protein content of wheat flour from four Indian cultivars whereas it was lower than those reported several researchers (Lorenz et al 1979;Giami 2001;Giami and Barber 2004). Previous reports on ash content of wheat flour are in the range of 0.44-0.7 %, for wet and dry gluten (Lorenz et al 1979;Giami 2001).…”
Section: Wheat Flour Qualitymentioning
confidence: 67%
“…Flour contained ash content (0.48 %), SDS, sedimentation value (30.19 %) and diastatic activity of 265 mg/10 g flour. Singh et al(1993) reported similar protein content of wheat flour from four Indian cultivars whereas it was lower than those reported several researchers (Lorenz et al 1979;Giami 2001;Giami and Barber 2004). Previous reports on ash content of wheat flour are in the range of 0.44-0.7 %, for wet and dry gluten (Lorenz et al 1979;Giami 2001).…”
Section: Wheat Flour Qualitymentioning
confidence: 67%
“…The protein concentrates from Bambara groundnut flour (BGF) were prepared using the alkaline wet extraction process described by Deshpande & Cheryan [18] with little modification as reported by Giami & Isichei [19], for fluted pumpkin seeds. Fifty grams of sample was suspended in 300ml of 0.04M NaOH and the mixture was stirred at room temperature (28±1 o C) for 1h, using a mechanical shaker.…”
Section: Preparation Of Protein Concentratesmentioning
confidence: 99%
“…Sensory evaluation of the bread was carried out after baking using the method described by Giami & Barber [21] for fluted pumpkin cookies. A panel of twenty (20) consumers comprising staff and student from Rivers State University of Science and Technology, Port Harcourt, Rivers State, Nigeria was used.…”
Section: Sensory Evaluation Of the Fortified Breadmentioning
confidence: 99%
“…It is reported to be indigenous to the west tropical rain forest area of Nigeria [8]. It is grown in Nigeria for its vegetable and oil bearing seeds.…”
Section: Introductionmentioning
confidence: 99%